Pemetaan Kebisingan Aktivitas Kendaraan Berat Area Pembangunan Grand Mangku Bumi Residence Kendari - Buraerah, Muh. Fikruddin; Hasrul, Reza (Jurnal Kridatama Sains dan Teknologi, 2023)
The City of Kendari is being targeted for the development of infrastructure and the capacity of motorized vehicles which continues to increase. The construction of the Grand Mangku Bumi Residence has an impact on air pollution. The location of the Grand Mangku Bumi Residence development which is near the main road has resulted in residential conditions that are passed by heavy vehicles experiencing traffic noise that exceeds the quality standard limit of 55 dBA in accordance with noisy criteria according to KEP-48/MENLH/11/1996. This noise causes air pollution around the study site. The purpose of this study is to determine the value of noise non-empirically with a sound level meter due to material transportation activities. The method in this study is quantitative by observing environmental conditions, traffic volume, road geometric, vehicle noise, and vehicle speed. Noise data collection was carried out for 2 months, Monday-Friday representing working days and Saturday-Sunday representing holidays, from 07.00 WITA to 20.00 WITA. Measurements were made every 1 hour for 10 minutes with a Sound Level Meter Model TM-103. Noise mapping is done with the surfer application. The results of the study show that before construction there were 5 survey points that exceeded the quality standards permitted in KEP-48/MENLH/11/1996 and there were 14 points that exceeded the permitted quality standards with an average rate of increase in traffic volume of 46.5 pcu/hour during the construction of the Grand Mangku Bumi Residence. Therefore, the noise level prior to the construction of the Grand Mangku Bumi Residence was lower than during construction.Keywords : Noise Zone; Sound Level Meter; Traffic; Surfer Application.